Internet-Based Physical Activity Interventions. (January 2014) - Joseph, Rodney P.; Durant, Nefertiti H.; Benitez, Tanya J.; Pekmezi, Dorothy W.
This article provides a comprehensive review of Internet– and Website–based physical activity interventions targeting adult populations. Search procedures identified 72 unique Internet-based physical activity interventions published in peer-reviewed journals. Participants of the studies were predominately White, middle-aged (mean age = 43.3 years), and female (65.9%). Intervention durations ranged from 2 weeks to 13 months (median = 12 weeks). Forty-six of the studies were randomized controlled trials, 21 were randomized trials without a control condition, 2 were non–randomized controlled trials, and 3 used a single-group design. The majority of studies (n = 68) assessed outcomes immediately following the end of the intervention period, and 16 studies provided delayed postintervention assessments. Forty-four of the 72 studies (61.1%) reported significant increases in physical activity. Future directions for Internet-based physical activity interventions include increasing representation of minority and male populations in Internet-based efforts, conducting delayed postintervention follow-up assessments, and incorporating emerging technologies (ie, cellular and Smartphones) into Internet-based physical activity efforts.